Protein instability associated with AARS1 and MARS1 mutations causes trichothiodystrophy. Issue 18 (28th April 2021) - Botta, Elena; Theil, Arjan F; Raams, Anja; Caligiuri, Giuseppina; Giachetti, Sarah; Bione, Silvia; Accadia, Maria; Lombardi, Anita; Smith, Desiree E C; Mendes, Marisa I; Swagemakers, Sigrid M A; van der Spek, Peter J; et al.
Abstract: Trichothiodystrophy (TTD) is a rare hereditary neurodevelopmental disorder defined by sulfur-deficient brittle hair and nails and scaly skin, but with otherwise remarkably variable clinical features. The photosensitive TTD (PS-TTD) forms exhibits in addition to progressive neuropathy and other features of segmental accelerated aging and is associated with impaired genome maintenance and transcription. New factors involved in various steps of gene expression have been identified for the different non-photosensitive forms of TTD (NPS-TTD), which do not appear to show features of premature aging. Here, we identify alanyl-tRNA synthetase 1 and methionyl-tRNA synthetase 1 variants as new gene defects that cause NPS-TTD. These variants result in the instability of the respective gene products alanyl- and methionyl-tRNA synthetase. These findings extend our previous observations that TTD mutations affect the stability of the corresponding proteins and emphasize this phenomenon as a common feature of TTD. Functional studies in skin fibroblasts from affected individuals demonstrate that these new variants also impact on the rate of tRNA charging, which is the first step in protein translation. The extension of reduced abundance of TTD factors to translation as well as transcription redefines TTD as a syndrome in which proteins involved in gene expression are unstable.